2008
DOI: 10.1007/s00264-008-0524-0
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic abilities of bone marrow stromal cells are not defective in patients with osteonecrosis

Abstract: We investigated whether the proliferation activities and osteogenic capacities of bone marrow stromal cells (BMSCs) are depressed in patients with osteonecrosis of the femoral head (ONFH). BMSCs were isolated from fresh bone marrow of the iliac crests of 54 donors and were differentiated into osteogenic lineage in vitro. The results of 27 consecutive patients with ONFH (16 idiopathic and 11 alcohol-induced) were compared with those of 27 patients with a nonnecrotic hip disorder. The proliferative activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
(41 reference statements)
3
10
0
Order By: Relevance
“…Previous data from Yoo et al . described the good osteogenic abilities in vitro of BMSCs from patients with osteonecrosis [ 45 ]. Altogether, these data indicate that the use of autologous BMSCs for a therapeutic treatment of ONFH is a feasible strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from Yoo et al . described the good osteogenic abilities in vitro of BMSCs from patients with osteonecrosis [ 45 ]. Altogether, these data indicate that the use of autologous BMSCs for a therapeutic treatment of ONFH is a feasible strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous researches confirmed that the good osteogenic function of BMSCs is existence about patients with alcohol-induced ONFH [ 21 , 22 ]. Our research aimed to explore the affection power of genetic factors for alcohol-induced ONFH.…”
Section: Discussionmentioning
confidence: 94%
“…H-1101-108-353) using a modification of the procedure described by Pittenger et al 32,33 To prepare the CM from hUCB-MSCs, the cells were detached upon reaching 80% confluency in a 9-cm 2 dish and transferred into an a-minimum essential medium (MEM) containing 2% fetal bovine serum (FBS). After incubation for 24 h, the supernatant was collected and sterilized by the passage through a 0.45-mm-pore filter.…”
Section: Isolation and Culture Of Hucb-mscs And Preparation Of CMmentioning
confidence: 99%